Developing Brazil with Prosperity Zones - Litvay, Francisco; Soruco, Marcelo (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2020)
This paper proposes to demonstrate Prosperity Zones as an alternative to improve governance and help develop Brazil and its macro-regions through the creation of cities with competitive legal structures. The shortcomings of traditional governments are first examined, and then their underlying problems are analyzed. After an explanation of the Prosperity Zone model and its origin, the document continues to demonstrate how this system solves the main problems of political economy present in contemporary governments, referring as an example to the effectiveness of less technological special jurisdictions already established in Brazil, such as the Manaus Free Zone. Finally, recommendations and forecasts are presented regarding its implementation in Brazilian territory.